2017
DOI: 10.1038/onc.2017.256
|View full text |Cite
|
Sign up to set email alerts
|

High-depth, high-accuracy microsatellite genotyping enables precision lung cancer risk classification

Abstract: There remains a large discrepancy between the known genetic contributions to cancer and that which can be explained by genomic variants, both inherited and somatic. Recently, understudied repetitive DNA regions called microsatellites have been identified as genetic risk markers for a number of diseases including various cancers (breast, ovarian and brain). In this study, we demonstrate an integrated process for identifying and further evaluating microsatellite-based risk markers for lung cancer using data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Four out of 10 genes have been studied as driver genes of LUAD. The tenth gene “HERC2P3” contains a microsatellite locus that can precisely discriminate LUAD samples and non-tumor samples (Velmurugan et al, 2017). As for three competing algorithms, Tables 3–5 show their prediction results.…”
Section: Resultsmentioning
confidence: 99%
“…Four out of 10 genes have been studied as driver genes of LUAD. The tenth gene “HERC2P3” contains a microsatellite locus that can precisely discriminate LUAD samples and non-tumor samples (Velmurugan et al, 2017). As for three competing algorithms, Tables 3–5 show their prediction results.…”
Section: Resultsmentioning
confidence: 99%
“…This discrepancy is slowly changing. So far, germline microsatellite markers have been proposed for breast cancer (26,27), ovarian cancer (27) and lung cancer (28). The Comparative Analysis of Germline Microsatellites (CAGm) database presented in this work may expedite the discovery of additional markers by serving as a catalog of germline genotypes in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Trinucleotide repeats can have dramatic effects and are known to increase the risk of particular genetic diseases such as Huntington’s disease, spinocerebellar ataxia and myotonic dystrophy (25). Second, recent studies have demonstrated the diagnostic potential of microsatellites for a limited number of cancers: breast cancer (26,27), ovarian cancer (27) and lung cancer (28). Third, germline DNA is easily obtained and therefore a well-suited target for genomic based testing for somatic microsatellite polymorphisms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, microsatellites expansion has been proved to cause more than 30 neurological and neuromuscular diseases [11], for instance, epilepsy caused by abnormal expansions of TTTCA and TTTTA repeats [12], Huntington disease cansed by CAG repeats [13], etc. Also it is related to lung cancer [14], gastric cancer [15], etc. The occurrence of microsatellites in non-coding regions are also associated with diseases by regulating gene expression, such as Friedreich Ataxia [16].…”
Section: Introductionmentioning
confidence: 99%